Computed body tomography with MRI correlation, on CD-ROM - Lee, Joseph K.T; Sagel, Stuart S.; Stanley, Robert J.; Heiken, Jay P.; Lippincott Williams & Wilkins (Philadelphia : Lippincott-Raven, 1998)
This CD offers new guide from leading clinicians on the latest applications of computed tomography and magnetic resonance imaging, with spiral CT incorporated throughout.
System requirements: Windows 3.1 or higher; 8 MB of RAM; 11 MB of free hard disk space
System requirements: Macintosh ;8 MB of RAM; 8 MB of free hard space; System 7.1 or higher
Keywords: Tomography, X-Ray Computed; Magnetic Resonance Imaging; Tomography, Emission-Computed